Trichofolliculoma On Scalp - Sodeify Manoochehr; Aghaei Shahin (Wolters Kluwer Medknow Publications, 2004)
Trichofolliculoma is a congenital malformation with an excess of hair which are usually increased not only in number, but also in length, thickness and pigmentation. The tumor may be multiple, and is usually located on cheek and nose, but may be seen in other areas as well. We present a case of trichofolliculoma on scalp in a 17 year old boy, presenting as a small papule that had a bunch of fine, white hair.